Development of Blended Learning in Flipped Learning-Based in Islamic Education Learning During the Covid-19 Pandemic - Anggraeni , Dewi; Bahri , Saiful (Al-Insyiroh: Jurnal Studi Keislaman, 2022)
This study aims to develop a learning model for Islamic Education based on Flipped Learning. The method used in this research is the method of research and development (Research & Development). The R&D method is a research method used to produce products and test their effectiveness. The model used by the researcher adapted the ADDIE development model. Based on the needs analysis stage, student analysis, curriculum analysis, material analysis, and analytical analysis and learning methods are carried out. There is a need for the development of PAI learning media with a local wisdom approach. Media development based on the validity test carried out by media experts and material experts obtained the average validation result by media experts, namely 87.133%. In comparison, the impact of the validity test by material experts was 86.75%. The results of field trials on users are excellent. The average score of students was 86.5%, and educators were 86.5%.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â